ANALYSIS OF THE IMPLEMENTATION OF DUTIES AND FUNCTIONS IN REGIONAL TECHNICAL IMPLEMENTATION UNIT FOR THE PROTECTION OF WOMEN AND CHILDREN (UPTD-PPA) IN PROVIDING PROTECTION FOR CHILDREN VICTIMS OF VIOLENCE IN DUMAI CITY - Tsania Annisa; Sitti Rahmah (Yayasan Wayan Marwan Pulungan, 2024)
This research aims to find out how the duties and functions of the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD-PPA) are implemented in protecting child victims of violence in Dumai City. The research method used in this research is qualitative research where a case study was conducted in the city of Dumai. Data collection techniques are carried out through observation, interviews and documentation. The results of this research indicate that the implementation of the duties and functions of the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD-PPA) in protecting child victims of violence in Dumai City has not been fully implemented. This is proven by the existence of several indicators whose implementation has not been good. Meanwhile, the obstacle in implementing cases of violence against children in Dumai City is the difficulty of handling cases because the number of reports received exceeds the number of available workers. As a result, the case handling process becomes slow due to a lack of personnel to handle all incoming reports and a lack of public knowledge and awareness.